“PROBLEMS IN A MULTILINGUAL ENVIRONMENT” - Maxamadova Zilola,; Pardayev To'lqin, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  This  article  examines  the  challenges  that  arise  in  multilingual environments  where  people  from  diverse  linguistic  backgrounds  interact.  While multilingualism promotes cultural richness and broader communication, it also creates barriers  in  education,  workplace  communication,  social  integration,  and  policy-making. By analyzing these problems and suggesting possible solutions, this paper emphasizes  the  importance  of  developing  inclusive  strategies  to  ensure  effective interaction in multilingual societies.